2012
DOI: 10.1248/bpb.b12-00293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol Pretreatment on Skin Permeation of Drugs

Abstract: It has been demonstrated that ethanol (EtOH) can enhance skin permeation of drugs when simultaneously applied with drugs. However, only a few studies have reported on the pretreatment effect of EtOH on skin permeations. In this study, the pretreatment effects of EtOH on skin permeation of drugs were investigated by measuring changes in skin permeation and electrical skin resistance. Permeabilities of deuterium oxide (D 2 O), isosorbide mononitrate (ISMN), isosorbide dinitrate (ISDN), calcein sodium (CA-Na), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
(21 reference statements)
2
16
0
Order By: Relevance
“…The decreasing ratio in the skin permeation of FD-4 obtained in the present study was higher than our previous findings for the permeation of calcein (molecular weight (MW); 645) after a pretreatment with a high concentration of EtOH. 25) On the other hand, the reciprocal of electrical skin resistance 34) obtained in the present study suggests that ion transport through skin was detected under all conditions independently of the EtOH concentration. The low reciprocal of skin resistance of ionized LC has been attributed to low ion concentrations in the buffered solution (we used 1/30 mM PB instead of PBS) in the donor compartment, and the relationship between skin resistance and the EtOH concentration was similar to that of the other drugs.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The decreasing ratio in the skin permeation of FD-4 obtained in the present study was higher than our previous findings for the permeation of calcein (molecular weight (MW); 645) after a pretreatment with a high concentration of EtOH. 25) On the other hand, the reciprocal of electrical skin resistance 34) obtained in the present study suggests that ion transport through skin was detected under all conditions independently of the EtOH concentration. The low reciprocal of skin resistance of ionized LC has been attributed to low ion concentrations in the buffered solution (we used 1/30 mM PB instead of PBS) in the donor compartment, and the relationship between skin resistance and the EtOH concentration was similar to that of the other drugs.…”
Section: Discussionsupporting
confidence: 51%
“…25) Our findings demonstrated that the skin permeation of hydrophilic drugs was increased and decreased by pretreatments with low and high concentrations of EtOH, respectively. We then speculated that EtOH may have affected the permeation pathway of these drugs.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Typically, TSS contains a volatile alcohol as a carrier solvent. Volatile alcohol impact on skin permeation from volatile transdermal products is minimal due to its rapid evaporation; for alcohol to enhance skin permeation alcohol--skin contact time is critical [56][57][58]. In a recent study to assess alcohol enhanced skin permeation from disinfectant formulations, it was concluded that alcohol did not induce clinically relevant dermal absorption enhancement within 1 h after disinfectant application.…”
Section: Impact Of Volatile Solventmentioning
confidence: 99%
“…However, the permeation of caffeine decreased at the highest ethanol concentration, because highly concentrated ethanol dehydrates the skin membrane and reduces the skin permeation of drugs [21]. Our previous study also found that the skin permeability of hydrophilic drugs was increased but inversely decreased by low and high concentration of ethanol, respectively [22]. In addition, X-ray diffraction data confirmed that low concentrations of ethanol disturbed the short lamellar structure of SC lipids, but the high concentration caused an aligned structure [23].…”
Section: Resultsmentioning
confidence: 99%